Initial Upper Paleolithic in the Zagros Mountains - Shoaee, Mohammad Javad; Vahdati Nasab, Hamed; Storozum, Michael; Frenzel, Peter; Akhavan Kharazian, Mohammad; Fernandes, Ricardo; Hashemi, Seyed Milad; Jayez, Mozhgan; Amano, Noel; Marzban Abbasabadi, Behrokh; Aalipoor, Mehdi; Lucas, Mary; et al. (Frontiers in Earth Science, 2024)
The Iranian Plateau and the Zagros Mountain chain, located at the crossroads of Africa and Eurasia, occupies a critical geographical position in out of Africa scenarios, sitting astride a major dispersal corridor into southern and central Asia. Yet, the region's role in human population expansions remains under-investigated. Here, we present findings from new excavations at Pebdeh Cave, a site located in the southern zone of the Zagros Mountains. Pebdeh contained a well-defined layer dating to ~42-40,000 years ago (ka), with Levallois elements alongside laminar reduction. This transitional feature in the Zagros was not dated and recorded before and given its similarity to Western and Central Asian industries with respect to chronology and technological features, we define it here as the Zagros Initial Upper Paleolithic (IUP). Though Late Middle Paleolithic and Early Upper Paleolithic technologies have been identified in the Zagros in the time period ranging between 50-40 ka, suggesting the presence of Neanderthals and modern humans in the mountainous region, the overall abrupt and constrained chronology of the IUP at Pebdeh, together with the penecontemporaneous appearance of other Upper Paleolithic sites in the Zagros Mountains, is compatible with a population expansion of Homo sapiens rather than an autochthonous development.